IMPLEMENTASI ALGORITMA WINNOWING PADA PLATFORM E-LEARNING UNTUK SISTEM PENILAIAN OTOMATIS JAWABAN ESSAY - Sari, Fifi Novalita; Harlanu, Muhammad; Widodo, Djoko Adi (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
The scoring system automatically answers the description exam is a way to facilitate and accelerate the process of assessment answers the description (essay). The system is performed by measuring similarity between answers learners answers with the answer key, this can be done by applying the method of string matching algorithm that uses Winnowing. The purpose of this study was to develop a ratings feature essay answers on Learning Management System, examine the effectiveness of assessment of learning outcomes with features developed, and determine differences in learning outcomes assessment using an automated system with manual systems. The scoring system answers to essay automatically on Learning Management System (LMS) used an experimental method which is one shot case study, in this case means there is no pretest and only a posttest, with a test system for students to investagate comparison of changes in the results of the study treated , Based on the analysis using the results of the questionnaire using descriptive analysis, so it can be concluded that there are significant differences between the value of the correction system with manual correction based on the description of each of the questions on the results that have been obtained.